Elevated INR in a COVID-19 patient after concomitant administration of azvudine and anticoagulants - Zhang, Xi; Jiao, Fengwei; Li, Guangrun; Yu, Xiaojia; Pei, Yuqing; Zhang, Ying; Wang, Zihui; Li, Pengfei (Frontiers in Pharmacology, 2023)
Background: Azvudine (FNC) is a promising treatment candidate for managing coronavirus disease 2019 (COVID-19). However, drug interactions with azvudine have been poorly studied, especially with no reported cases of azvudine with anticoagulants such as warfarin and rivaroxaban. Case summary: The patient was diagnosed with lower limb venous thrombosis and took warfarin regularly. The international normalized ratio (INR) was stable (2.0–3.0). However, the INR increased to 7.52 after administering azvudine. The patient had no other factors justifying this change. This increase in INR occurred again with the administration of azvudine in combination with rivaroxaban, and the INR increased to 18.91. After azvudine administration was stopped, the INR did not increase when rivaroxaban was used alone. Conclusion: Azvudine, warfarin, and rivaroxaban might have previously unidentified drug interactions that increased the INR. Therefore, the INR must be closely monitored when they are concomitantly administered in COVID-19 patients.